The phloroglucinol calcitrinone A, a novel mitochondria-targeting agent, induces cell death in breast cancer cells. (April 2022) - El Gaafary, Menna; Saber, Fatema R.; Mahrous, Engy A.; Ashour, Rehab M.; Okba, Mona M.; Jin, Lu; Lang, Sophia J.; Schmiech, Michael; Simmet, Thomas; Syrovets, Tatiana
Abstract: Breast cancer is the most common cancer and the leading cause of cancer-related mortality among females worldwide. From the leaves of Callistemon citrinus, we have isolated a novel phloroglucinol dimer, calcitrinone A, and analyzed its potential anticancer activity using the triple-negative breast cancer cell line MDA-MB-231. Calcitrinone A decreased the total intracellular ATP levels, inhibited proliferation, and induced apoptosis in MDA-MB-231 cells, but was less toxic to peripheral blood mononuclear cells. The antiproliferative and apoptosis-inducing effects of calcitrinone A were confirmed in vivo using breast cancer xenografts grown on chick chorioallantoic membranes. Mechanistic analysis showed mitochondrial membrane-potential dissipation and interference with energy-yielding processes resulting in cell accumulation in the S phase of the cell cycle. Seahorse assay analysis revealed an early inhibition of mitochondrial oxidative phosphorylation (OXPHOS). At the molecular level, calcitrinone A inhibited activity of the succinate-coenzyme Q reductase (SQR) (mitochondrial complex II). In silico docking identified the coenzyme Q binding pocket as a possible high affinity binding site for calcitrinone A in SQR. Inhibition of complex II was accompanied by strong elevation of mitochondrial superoxide and cytoplasmic ROS. Calcitrinone A might be a promising anticancer lead compound acting through the interference with the mitochondrial complex II activity. Graphical abstract: Image 1 Highlights: Calcitrinone A is a novel phloroglucinol dimer isolated from Callistemon citrinus. It induces cytotoxicity in MDA-MB-231 breast cancer cells in vitro and in vivo. It inhibits OXPHOS, increases ROS, and affects the mitochondrial integrity. At the molecular level, calcitrinone A inhibits the mitochondrial complex II.